ANALYSIS OF TEACHER UNDERSTANDING ON MATHEMATICAL LITERACY PROBLEMS (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2020)
The Indonesian government has been promoting the National Literacy Movement since 2016. However, teachers’ readiness to promote mathematical literacy skills in the classroom are deficient. This research aims to analyze secondary school mathematics teachers’ understanding of mathematical literacy problems. We carried out a survey study involving 32 mathematics teachers in Bandung-West Java. In this survey, each teacher was requested to send two mathematics problems considered as mathematical literacy problems via Google Form. The result of the analysis showed that only one-fourth of the teachers are familiar with mathematical literacy problems. Implications for mathematics educations is discussed.
Keywords: Mathematical Literacy; Mathematical Literacy Problems; National Literacy Movement; Mathematics Education